Investigating the impact of copper leaching on the combustion and emissions characteristics of a direct injection diesel engine - La Porta, Corrado (2024)
In recent years, an increasing effort towards reducing the use of diesel engine as a consequence to the “Volkswagen scandal” has arisen. Despite those efforts, it is very difficult to replace diesel engines due to their excellent characteristics such us high power to weight ratio and reliability. Especially some sectors such as HDV and ships have not reliable replacement to diesel engines. In this scenario, much interest was drawn to replace diesel with carbon neutral substitutes (e.g. biodiesel, HVO) and/or to improve diesel through the addition of additives. Additives are added as nanomaterials and mixed to diesel/biodiesel. Although additives successfully improve combustion and emissions, a few challenges have still not been met such as having even smaller additive particle size, reducing the PN emissions and reducing the production of nanofuels from a two-step method to a one-step method. This research has proven that it is possible to control the rate of copper release, therefore achieving a one-step method with reduced size of the additive. Copper was released in diesel through a fuel conditioning device made of copper that was subjected to electromagnetic field. This device was installed in a 2.2 L Ford Puma Duratorq diesel engine. The engine was run at 3 conditions representing low to medium speed/load. The addition of 0.2 ppm of copper in diesel has led to a reduction in combustion duration up to 1 CAD and in soot emissions up to 28%. When copper was replaced with Teflon and only the electromagnetic field was left, no improvement in emissions nor combustion were observed, therefore demonstrating that the increasing concentration of copper played a central role in the observed improvement. Subsequently, a small fuel rig was made to assess how temperature and magnetic field were affecting the corrosion. Increasing temperature of copper to 60 ℃ increased corrosion rate by 44% compared to baseline conditions (no heat or magnetic field applied). However, the application of a magnetic field increased the corrosion rate of copper in diesel by 2-3.5 times, therefore suggesting that the application of the electromagnetic field was boosting copper contamination in diesel. Besides, 3 sets of permanent magnets were investigated and the corrosion rate increased with increasing magnetic field strength. The combined effect of temperature and magnetic field provided the highest corrosion rate (257% more than baseline). Other metals were not successfully leached in diesel, although it was possible to deposit platinum oxides onto copper plates and then leach platinum oxides in diesel.